Energy efficiency in households: The effectiveness of different types of messages in advertising campaigns. (November 2017) - Casado, Fernando; Hidalgo, M. Carmen; García-Leiva, Patricia
Abstract: The current enormous levels of energy waste are among the main culprits for climate change. Research in the field of energy has suggested the need for more effective public awareness advertising campaigns to modify consumer behaviour and reduce waste. An experimental study was conducted to analyse the effectiveness of various types of information to improve behavioural intentions in relation to energy efficiency. A two-by-two factorial design was followed in which the independent variables were economic benefits and specific behavioural guidelines related to energy efficiency. A control group was also included. The dependent variables were the degree of informational persuasion in the campaign and future behavioural intention. The study included 176 participants. Our results confirm that messages on energy efficiency combining specific behaviour guidelines and economic benefits are more effective than those based on either type of information alone. Also, specific messages are found to be more effective than generic ones. Highlights: Specific messages to promote saving energy are more effective than generic messages. The combination of behavioural guidelines and economic benefits is more persuasive. Behavioural guidelines and economic benefits increase intentions to save energy.